2019
DOI: 10.1017/s0272263119000482
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Lexical Tones Difficult to Learn?

Abstract: L2 sounds present different kinds of challenges to learners at the phonetic, phonological, and lexical levels, but previous studies on L2 tone learning mostly focused on the phonetic and lexical levels. The present study employs an innovative technique to examine the role of prior tonal experience and musical training on forming novel abstract syllable-level tone categories. Eighty Cantonese and English musicians and nonmusicians completed two tasks: (a) AX tone discrimination and (b) incidental learning of ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 72 publications
1
22
0
Order By: Relevance
“…Since our first study (Pelzl et al, 2019), the particular difficulty of disyllabic, as opposed to monosyllabic tone words, has remained an open question. Studies with naïve, novice, and intermediate proficiency L2 participants have reported this pattern in tone category identification tasks (Broselow et al, 1987;Hao, 2018;Sun, 1998;see also;Chan and Leung, 2020). In a tone word training study with naive learners, Chang and Bowles (2015) found disyllabic words to be much more challenging than monosyllabic words.…”
Section: Three General Accounts Of Tone Difficultiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Since our first study (Pelzl et al, 2019), the particular difficulty of disyllabic, as opposed to monosyllabic tone words, has remained an open question. Studies with naïve, novice, and intermediate proficiency L2 participants have reported this pattern in tone category identification tasks (Broselow et al, 1987;Hao, 2018;Sun, 1998;see also;Chan and Leung, 2020). In a tone word training study with naive learners, Chang and Bowles (2015) found disyllabic words to be much more challenging than monosyllabic words.…”
Section: Three General Accounts Of Tone Difficultiesmentioning
confidence: 91%
“…This is the real-time process that links the perceived phonetic signal to phonolexical representations encoded in long-term memory. It roughly corresponds to the phonological step of the phonetic-phonological-lexical continuum (Wong and Perrachione, 2007;Chan and Leung, 2020), but we wish to stress the lexical aspect of this process, along with the phonological. For L2 learners, years of experience attending only to the important phonetic features of their L1 might interfere in real-time word recognition.…”
Section: Three General Explanations For L2 Tone Word Processing Difficultiesmentioning
confidence: 99%
“…For instance, Poltrock et al (2018) showed that Mandarin participants outperformed French listeners in recalling Cantonese pseudowords that contrasted in tone. Chan and Leung (2020) investigated the effects of L1 tonal status on the incidental 'phonological learning', which was defined as an intermediate step between tone perception and tone word learning (p. 4). They show that Cantonese participants outperformed English participants in the phonological learning of Thai tones, and suggest that Cantonese L1 tonal status facilitated the formation of syllable-level tone categories required for utilizing tones at the word level.…”
Section: L1-specific Factors In Tone Word Learningmentioning
confidence: 99%
“…Though not focused on processing per se, recent work by Chan and Leung (2020) is also amenable to processing accounts in that it is deals with statistical learning mechanisms. They examined Cantonese and English L1 participants' abilities to pick up on co-occurrence patterns of syllable-initial segmental cues and specific tones (i.e., syllables beginning with aspirated stop consonants always had rising tones; syllables beginning with an approximant always had falling tones).…”
Section: Processing Biases Could Drive L2 Tone Word Errorsmentioning
confidence: 99%